IMPLEMENTING IT GOVERNANCE TO LEVERAGE IS/IT VALUE IN AN ORGANIZATION CASE STUDY MIS DEPARTMENT OF PT. XYZ - Wongso, Fery; Kasman, Hendra (International Journal of Business and Information Technology, 2020)
The objective In this research are to know what are the indicator of good performance, what are the CSF, KPI & KGI for ?, how do we measure and compare both of them? The Methodology used for this research is based on framework released by IT Governance Institute but it is being modified (minor changes) for a certain purpose. Based on our analysis the average IT Maturity level of fourteen IT process at MIS Department PT. XYZ is 2.83 more higher than the result from ISACA survey among 47 US company only 2.62. The IT management of PT. XYZ should not make their self satisfied with this result, as multinational company they have to aware for improving regarding their IT governance. Our research also provided & equipped set action plan & methodology for management to achieve the better IT Maturity Level. There are some recommendations for the IT management in order to achieve the better namely: 1. IT Maturity Level Management have to perform continuous improvement, especially for some IT process such as DS1 (Define Service Level) the lowest maturity rating, DS4 (Ensure Continuous Services) the second lowest maturity rating, PO9 (Assess Risk) & PO10 (Manage Project) the third lowest maturity rating. 2. Management also have to consider for doing the full step methodology in the next assessment. 3. Management have to consider for develop performance measurement tools, this tools will help management to manage IT resources & process for aligning with the business objective